Nacionalismo, não-violência e os novos atores engajados na política contenciosa brasileira : o caso do Movimento Brasil Livre (MBL) - Machado, Luana Barbosa (2017)
The present dissertation aims to analyze the Free Brazil Movement (MBL). One of the questions to be addressed in this research is to explore, understand and to describe the formation of new actors engaged in the contentious politics of Brazilian society. Based on the theory of confrontation, the research sought to reflect on the issues that make up the emergence of this new collective actor, the possible context that facilitated its emergence in the political-social scenario of the country. It also seeks to problematize the modus operandi in which the MBL conducted its guidelines, claims and objectives. The analysis of these issues is anchored in the aspects of (a) a description of the sociohistorical context in which the emergence of these actors linked to the political right occurs, (b) the prognosis of their collective actions, such as the identification of action repertoires and the analysis of frames from the multi-thematic milestones nationalism and non-violence. For this purpose, documents of a different nature produced by MBL were analyzed based on qualitative methodology.